Peru : Financial Sector Assessment Program-Detailed Assessment of Observance. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2018)
The overall quality of Peru's supervisory approach and regulation of the banking sector is strong. Some areas for enhancement remain. A key area that needs strengthening relates to the powers and regulatory framework for consolidated and cross-border supervision. The FSAP undertook a full graded Basel Core Principles (BCP) assessment of the essential criteria. The 2011 BCP update assessment found that bank regulation and supervision was of high quality and no principles were scored non-compliant or materially non-compliant. The current assessment shows that the SBS has maintained and further enhanced its regulatory and supervisory framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Peru